J. Harris, Pastoral Theology. A Black – Church Perspective, Minneapolis, Fortress Press, 1991, 160 pp - Ramos, Gerardo Daniel (2007)
Fil: Ramos, Gerardo Daniel. Pontificia Universidad Católica Argentina; Argentina